Enhanced Metabolic Stress Augments Ischemic Preconditioning for Exercise Performance - Slysz, Joshua T.; Burr, Jamie F. (Frontiers in Physiology, 2018)
Purpose: To identify the combined effect of increasing tissue level oxygen consumption and metabolite accumulation on the ergogenic efficacy of ischemic preconditioning (IPC) during both maximal aerobic and maximal anaerobic exercise. Methods: Twelve healthy males (22 ± 2 years, 179 ± 2 cm, 80 ± 10 kg, 48 ± 4 ml.kg−1.min−1) underwent four experimental conditions: (i) no IPC control, (ii) traditional IPC, (iii) IPC with EMS, and (iv) IPC with treadmill walking. IPC involved bilateral leg occlusion at 220 mmHg for 5 min, repeated three times, separated by 5 min of reperfusion. Within 10 min following the IPC procedures, a 30 s Wingate test and subsequent (after 25 min rest) incremental maximal aerobic test were performed on a cycle ergometer. Results: There was no statistical difference in anaerobic peak power between the no IPC control (1211 ± 290 W), traditional IPC (1209 ± 300 W), IPC + EMS (1206 ± 311 W), and IPC + Walk (1220 ± 288 W; P = 0.7); nor did VO2max change between no IPC control (48 ± 2 ml.kg−1.min−1), traditional IPC (48 ± 6 ml.kg−1.min−1), IPC + EMS (49 ± 4 ml.kg−1.min−1) and IPC + Walk (48 ± 6 ml.kg−1.min−1; P = 0.3). However, the maximal watts during the VO2max increased when IPC was combined with both EMS (304 ± 38 W) and walking (308 ± 40 W) compared to traditional IPC (296 ± 39 W) and no IPC control (293 ± 48 W; P = 0.02). Conclusion: This study shows that in a group of participants for whom a traditional IPC stimulus was not effective, the magnification of the IPC stress through muscle contractions while under occlusion led to a subsequent exercise performance response. These findings support that amplification of the ischemic preconditioning stimulus augments the effect for exercise capacity.